2014
DOI: 10.1186/s13014-014-0232-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the value of ENI in radiotherapy for cervical and upper thoracic esophageal cancer: a retrospective analysis

Abstract: BackgroundA retrospective study to compare the failure patterns and effects of elective nodal irradiation (ENI) or involved field irradiation (IFI) for cervical and upper thoracic esophageal squamous cell carcinoma (SCC) patients.MethodsOne hundred and sixty nine patients with the cervical and upper thoracic esophageal SCC were analyzed retrospectively; 99 patients (59%) underwent IFI and 70 patients (41%) received ENI. We defined “Out-PTVifi in-PTVeni metastasis” as lymph node metastasis occurring in the cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 15 publications
2
43
0
Order By: Relevance
“…Liu et al studied 169 elderly EC patients receiving IFI and ENI and the results showed that no significance difference was seen for OS and in-field recurrence and distal organ metastasis between the two groups [20]. Our results also showed that no significant difference was found between IFI and ENI in relation to the reported outcomes and toxicities in these studies.…”
Section: Discussionsupporting
confidence: 68%
“…Liu et al studied 169 elderly EC patients receiving IFI and ENI and the results showed that no significance difference was seen for OS and in-field recurrence and distal organ metastasis between the two groups [20]. Our results also showed that no significant difference was found between IFI and ENI in relation to the reported outcomes and toxicities in these studies.…”
Section: Discussionsupporting
confidence: 68%
“…After reading the abstracts, twenty were excluded for repeated published data, two for using 2-dimensional technology, fouthteen for being non-case-control studies. Eventually, nine studies involing 1143 ESCC patients were included in this meta analysis [4][5][6][7][8][9][10][11][12]. The basic characteristics and results of included studies were shown in Tables 1 and 2.…”
Section: The Retrieval Results and Quality Evaluationmentioning
confidence: 99%
“…Liu M et al [11] 2014 169 I~IV IFI: a 1 cm margin was added around GTV, but 3cm margins in the esophageal long axis superiorly and inferiorly to encompass potential submucosal invasions. ENI: covered supraclavicular area with the upper margin at the caudal edge of cricoid cartilage, inferior margin at the sternal notch.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective randomized trial, Ma et al 21 compared eni with ifi in patients with cervical and upper thoracic eca, observing no significant difference in the 3-year os or locoregional control rate between the ifi and eni groups (32.0% and 80.1% vs. 41.3% and 85.7% respectively). Liu et al 22 noted that out-of-field regional cervical node metastasis occurred in 8% of the ifi group and 10% of the eni group in patients with cervical and upper thoracic eca. Use of eni did not result in better os or long-term control in cervical lymph nodes.…”
Section: Discussionmentioning
confidence: 99%